Post a New Question


posted by on .

I am having trouble figuring this out.

(r - 6s + 3) + (7r + 5s) + (s+5)

  • algebra - ,

    Clear the parentheses.
    combine like terms.

  • algebra - ,

    I rewrite it according to terms.

    r+7r= 8r which is like saying 1+7=8 (then add back the variable)
    Same applies to the following:

    -6s+5s+s=0 which is like saying -6+5+1=0

    3+0+5= 8

    So you would end up with: 8r+8

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question